منهاج دعوة الشيخ محمد بن عبد الوهاب في كتاب التوحيد الذي هو حق الله على العبيد - Siti Rohmah; Husnul Khatimah (Rayah Al-Islam, 2020)
Sheikh Muhammad bin Abdul Wahhab, may God have mercy on him, is a renewed reformer of the reformist preaching movement this era. Many people of common sense make up their hearts by this da’wah. And this blessed da’wa spread to many spots on the face of the earth because it was in the right curriculum. But this da’wa’s opponents mutilated it to prevent people from accepting it, Rather, they consider that the book of monotheism that the Sheikh wrote for the sake of his da’wa is the "Black Book", which must be warned about the seriousness of its content. This humble research I wrote to show the merit of preaching Sheikh, may God have mercy on him, methodology through the book of monotheism, which is God’s right over slaves. I wrote this research on the descriptive curriculum. Through this research, I found that the da’wa of the Sheikh, may God have mercy on him, is based on the plans drawn up that confirm that it is not an invention as claimed by its opponents, but rather it is based on the Qur’an and Sunnah and what was the predecessor of the nation. His approach to the da’wa to monotheism through this book increases it advantages that distinguish it from the other.